Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
(x - 2)/3
(x - 4)/-5 or (-x + 4)/5
Step-by-step explanation:
this is an inverse function, and to solve an inverse function you would :
swap x and g(x) without bringing the x coefficient with it, just simply swap the variables. Then, solve for g(x), and that's it
the first question's answer is :
g(x) = 3x + 2
x = 3(g(x)) + 2
x - 2 = 3(g(x))
(x - 2)/3 = g(x)
the second one is:
g(x) = 4 - 5x
x = 4 - 5(g(x))
x - 4 = -5(g(x))
(x-4)/-5 = g(x)
g(x) = 3x + 2
y = 3x + 2
x = 3y + 2
3y = x - 2
y = x/3 - 2/3
inverse g(x) = (x - 2) / 3
g(x) = 4 - 5x
y = 4 - 5x
x = 4 - 5y
5y = 4 - x
y = 4/5 - x/5
inverse g(x) = (4 - x) / 5
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.